2006
DOI: 10.1016/j.cell.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

TUF Love for “Junk” DNA

Abstract: The widespread occurrence of noncoding (nc) RNAs--unannotated eukaryotic transcripts with reduced protein coding potential--suggests that they are functionally important. Study of ncRNAs is increasing our understanding of the organization and regulation of genomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 28 publications
5
92
0
5
Order By: Relevance
“…Recent studies have suggested that the transcriptomes of eukaryotic cells are much more complex than previously thought (20)(21)(22). In yeast, for example, a large number of nonannotated intergenic and antisense RNAs have been identified, and most protein-coding genes appear to have more than one transcriptional start site, a property that leads to both long and short transcripts from the same gene (19,23).…”
Section: Possible Contribution Of Transcriptional Noise To the Pool Omentioning
confidence: 99%
“…Recent studies have suggested that the transcriptomes of eukaryotic cells are much more complex than previously thought (20)(21)(22). In yeast, for example, a large number of nonannotated intergenic and antisense RNAs have been identified, and most protein-coding genes appear to have more than one transcriptional start site, a property that leads to both long and short transcripts from the same gene (19,23).…”
Section: Possible Contribution Of Transcriptional Noise To the Pool Omentioning
confidence: 99%
“…(Note: We will simply call them "ncRNAs" hereafter; they are sometimes called transcripts of unknown functions [TUFs]; see Mattick and Makunin 2006;Willingham and Gingeras 2006) Among the 768 "putative ncRNAs" which were identified from our previous human large-scale full-length cDNA analyses and annotation project, FLJ (Ota et al 2004), 49 were clearly confirmed to be transcribed in HEK293 cells by RT-PCR analyses (Supplemental Fig. 3 and Supplemental Table 6).…”
Section: Characteristic Features Of "Conserved" and "Non-conserved" Pprsmentioning
confidence: 99%
“…2H). A recent stream of reports have shown that ncRNAs serve important regulatory roles (Hornstein and Shomron 2006;Willingham and Gingeras 2006) via various mechanisms, such as by sense-antisense interactions with target transcripts and by directly interacting with proteins, thereby modulating the strength of proteinprotein interactions (Mattick and Makunin 2006). A recent estimate indicated that thousands of ncRNAs are transcribed from the human genome, and at least 30% of human genes are subject to regulation by these RNAs (Lewis et al 2005).…”
Section: Genome Research 1011mentioning
confidence: 99%
“…The microRNA pathway may contribute to post-transcriptional regulation of junD MicroRNA regulation of human genes is estimated to be prominent (X30% of human genes) (Willingham and Gingeras, 2006). The junD 681-nt 3 0 UTR harbors several microRNA target sequences predicted by the Sanger Institute database miRBase (JM Hernandez and K Boris-Lawrie, unpublished data).…”
Section: Introductionmentioning
confidence: 99%